Penggunaan Alat Pengeras Suara pada Lantunan Adzan dan Ayat-ayat Al-Qur’an Menurut Pendapat MUI Sumatera Utara dan KH. Mahmud Mukhtar - Nasution, Chairunnisa (Asian Journal of Islamic Studies and Da'wah, 2023)
Adzan means to announce, convey information about a problem. Whereas according to the term is "certain utterances to announce the time of Fardhu prayer", or in other words is "announcement about the entry of Fadhu prayer times with certain pronunciations". Mosques in Indonesia have started using loudspeakers as a tool to voice religious communication activities such as the call to prayer, recitation of verses from the Koran, tarhim, praise, dhikr, recitations, lectures to religious speeches. The purpose of this research is to find out the views of the Chairman of the North Sumatra MUI and KH. Mahmud Mukhtar regarding the case of the use of loudspeakers. From the type of research conducted in the field and from a circular issued by the Ministry of Religion Number 05 of 2021 concerning Regulations for Loudspeakers in Mosques and Musholahs. As well as the views of scholars regarding the call to prayer using loudspeakers.